A Discussion of Arctic Ionograms - Wagner, R. A.; Pike, C. P. (1980)
Example of arctic ionogram sequences, recorded on the AFCRL Flying Ionospheric Laboratory, are presented. The purpose of this paper is to show that: (a) ionogram sequences, recorded on arctic flights, facilitate the interpretation of oblique incidence echoes from E-and F-layer heights, (b) parameters of the arctic ionosphere can be mapped by using the 'auroral oval' as an ordering system, (c) vertical and oblique incidence echoes, appearing on ground station ionograms, can be interpreted in terms of the station's position relative to the auroral oval. The analysis of a three hour flight with 6 latitudinal scans underneath an auroral band shows the close relationship between auroral sporadic E echoes (Esa) and discrete aurora. The investigation of 49 latitudinal scans through the auroral oval during times of low magnetic activity revealed the existence of a particle produced E layer which is oval aligned, is 2 deg to 6 deg wide in corrected geomagnetic latitude and occurs at all corrected geomagnetic times. This layer produces the night E echoes. A new ionogram analysis procedure, which uses oblique incidence F-layer echoes, is demonstrated, and the feasibility of monitoring the latitude of the southern edge of the polar F-layer irregularity zone by using this new analysis procedure is demonstrated. Presented at the AGARD Technical Meeting in Lindau/Harz, Germany, Sep 1971.